IN SILICO EVALUATION OF BINDING INTERACTION AND ADME PROPERTIES OF NOVEL 5-(THIOPHEN-2-YL)-1,3,4-OXADIAZOLE-2-AMINE DERIVATIVES AS ANTI-PROLIFERATIVE AGENTS - ALI, YOUSEF SABAH; MAHDI, MONTHER FAISAL; RAZIK, BASMA M. ABD (International Journal of Applied Pharmaceutics, 2023)
Objective: The objective of this research was the virtual design of nine novel 1,3,4-oxadiazole derivatives and evaluating their antiproliferative activity as potential cyclin-dependent kinase 2 (CDK-2) inhibitors, which is a major component in cell cycle and proliferation. Methods: CDK-2 structure, PDB ID, 2R3J, co-crystallized with ligand SCJ from protein data bank was chosen to be docked with a series of nine 5-(thiophen-2-yl)-1,3,4-oxadiazol-2-amine derivatives to evaluate their abilities as potential anti-proliferative agents using Glide software (Maestro 11.4) one of Schrodinger software (Schrodinger, 2018). In addition, the pharmacokinetic properties of these derivatives were evaluated using the Swiss-ADME web tool. Results: Molecular modeling proposed that these 1,3,4-oxadiazole derivatives have powerful binding interaction with the active binding site of CDK-2 protein. In this article, two molecules have been observed as the most effective as they have docking scores of (-10.654 and-10.169 kcal/mol) respectively, whereas the binding score of the reference ligand was (-9.919 Kcal/mol) and most of the derivatives have fulfilled the Swiss-ADME parameters as potential orally active compounds. Conclusion: Novel 1,3,4-oxadiazole derivatives had shown promising results to be considered as lead compounds for developing new anti-proliferative agents as two compounds (P-1 and P-5) exhibit better docking score at 2R3J active site than the reference ligand with further biological and pharmacological evaluation required.